2020
DOI: 10.21203/rs.3.rs-25453/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PODXL Might Be a New Prognostic Biomarker in Various Cancers: A Meta-analysis and Sequential Verification with TCGA Datasets

Abstract: Abstract Background Several studies have investigated the associations between the podocalyxin-like protein (PODXL) expression quantity or locations and cancers survival, but the results were far from conclusive. Therefore, we proceeded a meta-analysis on PODXL in various human cancers to find its prognostic value and followed confirmation using the TCGA datasets. Methods We performed a systematic sear… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Our understanding of the role of lncRNAs in the progression and suppression of multiple tumors has resulted in novel opportunities to improve the diagnosis and treatment of malignancies [17,18]. Meta-analyses revealed that HOXD-AS1 [4], PODXL [19], and TP73-AS1 [20] were associated with the clinicopathological characteristics and prognosis of tumors. LncRNA prostate cancer-associated transcript 6 (PCAT6), which was first identified in keratinocytes, indirectly activates the Wnt/β-catenin pathway by interacting with KLHL12 in cervical cancer cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the role of lncRNAs in the progression and suppression of multiple tumors has resulted in novel opportunities to improve the diagnosis and treatment of malignancies [17,18]. Meta-analyses revealed that HOXD-AS1 [4], PODXL [19], and TP73-AS1 [20] were associated with the clinicopathological characteristics and prognosis of tumors. LncRNA prostate cancer-associated transcript 6 (PCAT6), which was first identified in keratinocytes, indirectly activates the Wnt/β-catenin pathway by interacting with KLHL12 in cervical cancer cells [21].…”
Section: Introductionmentioning
confidence: 99%